UTILIZATION OF STRAW IN FURNITURE DESIGN - Dharsono Dharsono; Sumarno Sumarno; N.R. Ardi Candra Dwi Atmaja (ARTISTIC : International Journal of Creation and Innovation, 2021)
Waste straw from rice harvesting in Indonesia, especially in the city of Solo and its surroundings, is very abundant and has not been utilized optimally yet. This is an economic potential if it is developed with furniture products which are the leading export products in the city. The purpose of this creation is (1) Utilization of straw rope as a material for supporting application in making furniture (2) Furniture products using wood and straw  applications. To achieve the goal, it takes steps or methods of creating works by utilizing emic and ethical data, including: experimentation, contemplation, and formation. From the creative process, it produces: (1) quality straw gyres and is suitable for use as supporting applications in furniture products, (2) Furniture products with wood and straw rope applications that are tested and feasible to produce.